2013
DOI: 10.3109/02770903.2013.831870
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-resistant asthma: more than meets the eye

Abstract: The challenges in making a diagnosis of glucocorticoid-resistant asthma may contribute to underestimating its prevalence and impact on patient care. Considerable progress has been made in identifying distinct phenotypes and mechanisms of glucocorticoid resistance; therefore the future of new drug development in management of asthma is promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 62 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…Smoking has been found to increase the risk of airway obstruction in adults who develop asthma after the age of 10 years [20]. This finding is relevant, since smoking is one of the risk factors that influence therapeutic response to corticosteroids, and is thus related to poor asthma control [21].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Smoking has been found to increase the risk of airway obstruction in adults who develop asthma after the age of 10 years [20]. This finding is relevant, since smoking is one of the risk factors that influence therapeutic response to corticosteroids, and is thus related to poor asthma control [21].…”
Section: Discussionmentioning
confidence: 82%
“…It is recommended that the ACT should be taken at different times of the year. We classified degree of asthma control into 4 categories based on ACT scores [9]: uncontrolled asthma (≤15 points), partly controlled asthma (16)(17)(18)(19), controlled asthma (20)(21)(22)(23)(24), and fully controlled asthma (25 points).…”
Section: Data Collection and Measurementsmentioning
confidence: 99%
“…Genetic studies for loci linked to susceptibility to asthma have identified candidates involved in immune function (e.g., innate immunity, immunoregulation, and T-cell differentiation), epithelial cell function (e.g., genes involved in epithelial biology and mucosal immunity), and genes involved in lung function and the remodeling of airways (6). Although it is well established that the development of asthma and asthmatic symptoms are dependent on an immune response, suppressing immune responses and antiinflammatory treatments only partially control symptoms, suggesting that cellular mechanisms outside the immune system add to the expression of this lung disease (3,7,8). Notably, a significant body of physiological data suggests that asthmatic symptoms may be significantly modulated by the nervous system (9, 10).…”
Section: Bronchospasms | Airway Inflammationmentioning
confidence: 99%
“…13, 14 It should be noted that steroid resistance frequently develops in patients. 15, 16, 17 Interestingly, in clinical investigations when MSCs are used to promote tissue repair in steroid-resistant patients, in whom inflammation continues, impressive results are often achieved. 5, 18 Unfortunately, the administration of MSCs has not been always successful.…”
mentioning
confidence: 99%